The challenge of preaching - Stott, John R. W. (William B. Eerdmans Publishing Company, 2015)
This book abridges and revises the text of Stott's Between Two Worlds: The Challenge of Preaching Today, first published in 1982, and updates it for our twenty-first-century context. Through Greg Scharf's abridging and updating work, John Stott's perspectives and insights on faithful, relevant preaching of the Word of God will benefit a new generation of preachers and preachers-to-be.